Formal Analysis of Distributed Shared Memory Algorithms - Atif, Muhammad; Mudassar Naseer; Ahmad Salman Khan (UMT Artificial Intelligence Review, 2022)
The memory coherence problem occurs while mapping shared virtual memory in a loosely coupled multiprocesses setup. Memory is considered coherent if a read operation provides the same data written in the last write operation. The problem has been addressed in the literature using different algorithms, although the correctness of a distributed algorithm remains questionable. Formal verification is the principal term for a group of techniques that routinely use an analysis established on mathematical transformations to conclude the rightness of the hardware or software behavior in divergence to dynamic verification techniques. The current study employed UPPAAL model checker to model the Dynamic Distributed algorithm for shared virtual memory given by K. Li and P. Hudak. The results showed that the Dynamic Distributed algorithm for shared virtual memory partially fulfils its functional requirements.